Colorimetric and fluorescent hydrazone-BODIPY probes for the detection of γ-hydroxybutyric acid (GHB) and cathinones. (November 2022) - Rodríguez-Nuévalos, Silvia; Costero, Ana M.; Parra, Margarita; Gil, Salvador; Arroyo, Pau; Sáez, Jose A.; Gaviña, Pablo; Ceroni, Paola; Fermi, Andrea
Abstract: Consumption and abuse of drugs is a general problem, which concerns our entire society. In some cases, drugs are used for recreational purposes; but in others, they are used to commit crimes such as Drug-Facilitated Sexual Assault (DFSA). In other cases, this consumption alters the consumer mood in such a way that risky situations can rise. In any case, detection of drugs in different environment is worthwhile. Here, two new chromogenic and fluorescent probes are reported. Detection of both cathinone derivatives and γ-hydroxybutyric acid (GHB) can be carried out with naked-eye with limits of detection of 0.4 μM and 0.3 μM for GHB and 2.0 μM for ephedrone. Selectivity in the presence of other drugs has been tested. Sensing mechanisms have been studied using different spectroscopic techniques and they have been also corroborated through theoretical calculations. Graphical abstract: Image 1 Highlights: Naked-eye colorimetric and fluorescent detection of the date-rape drug GHB, using two new hydrazone-BODIPY probes (1 and 2 ). Probe 1 in the presence of Cu(II) can detect synthetic cathinones, and also GHB, by fluorescence quenching. Limits of detection are 0.4 μM (probe 1 ) and 0.3 μM (probe 2 ) for GHB, and 2.0 μM for ephedrone.